Mortality among over 6 million internal and international migrants in Brazil: a study using the 100 Million Brazilian CohortResearch in context - Julia M. Pescarini; Emanuelle F. Goes; Priscila Fernanda Porto Scaff Pinto; Beatriz Pinheiro Schindler Dos Santos; Daiane B. Machado; Ibrahim Abubakar; Laura C. Rodrigues; Elizabeth B. Brickley; Liam Smeeth; Mauricio L. Barreto (Elsevier, 2023)
Summary: Background: To understand if migrants living in poverty in low and middle-income countries (LMICs) have mortality advantages over the non-migrant population, we investigated mortality risk patterns among internal and international migrants in Brazil over their life course. Methods: We linked socio-economic and mortality data from 1st January 2011 to 31st December 2018 in the 100 Million Brazilian Cohort and calculated all-cause and cause-specific age-standardised mortality rates according to individuals' migration status for men and women. Using Cox regression models, we estimated the age- and sex-adjusted mortality hazard ratios (HR) for internal migrants (i.e., Brazilian-born individuals living in a different Brazilian state than their birth) compared to Brazilian-born non-migrants; and for international migrants (i.e., people born in another country) compared to Brazilian-born individuals. Findings: The study followed up 45,051,476 individuals, of whom 6,057,814 were internal migrants, and 277,230 were international migrants. Internal migrants had similar all-cause mortality compared to Brazilian non-migrants (aHR = 0.99, 95% CI = 0.98-0.99), marginally higher mortality for ischaemic heart diseases (aHR = 1.04, 95% CI = 1.03-1.05) and higher for stroke (aHR = 1.11, 95% CI = 1.09-1.13). Compared to Brazilian-born individuals, international migrants had 18% lower all-cause mortality (aHR = 0.82, 95% CI = 0.80-0.84), with up to 50% lower mortality from interpersonal violence among men (aHR = 0.50, 95% CI = 0.40-0.64), but higher mortality from avoidable causes related to maternal health (aHR = 2.17, 95% CI = 1.17-4.05). Interpretation: Although internal migrants had similar all-cause mortality, international migrants had lower all-cause mortality compared to non-migrants. Further investigations using intersectional approaches are warranted to understand the marked variations by migration status, age, and sex for specific causes of death, such as elevated maternal mortality and male lower interpersonal violence-related mortality among international migrants. Funding: The Wellcome Trust.